Dog‐assisted interventions and outcomes for older adults in residential long‐term care facilities: A systematic review and meta‐analysis. (11th May 2020) - Jain, Briony; Syed, Shabeer; Hafford‐Letchfield, Trish; O'Farrell‐Pearce, Sioban
Abstract: Objective: To comprehensively review studies on dog‐assisted interventions (DAIs) among older people in residential long‐term care facilities (RLTCFs) and to provide an overview of their interventions, outcomes and methodological quality. Method: We searched 18 electronic databases to identify English articles (published January 2000–December 2019) reporting on well‐defined DAIs targeting older adults (≥65 years) in RLTCF. Data were extracted by two independent reviewers. Descriptive statistics were produced for quantitative studies, with key themes identified among qualitative studies. Where possible, estimates were pooled from randomised controlled trials using random effects meta‐analyses. Results: Forty‐three relevant studies (39 quantitative; 4 qualitative) were identified. The majority of quantitative studies were assessed as low‐quality according to the MMAT criteria ( n = 26, 67%). Almost half of the quantitative studies ( n = 18, 46%) found no significant changes over time or between groups across outcomes measured. The most salient intervention effects included improved social functioning ( n  = 10), reduced depressive symptoms ( n  = 6) and loneliness ( n  = 5). A random‐effects meta‐analysis revealed a medium effect in favour of DAT on reducing depressive or loneliness symptoms (pooled SMD: 0.66, 95%CI 0.21–1.11; I 2  = 50.5; five trials), relative to treatment as usual. However, compared to treatment as usual, no overall effect of DAI on activities of daily living was detected ( p  = .737). Key themes from qualitative studies included (a) animals as effective transitional objects, (b) the therapeutic value of pets and (c) the significance of the care environment and stakeholders in facilitating DAI. Implications for practice: The findings of this review indicate that while DAI has value for older people in RLTCF, challenges remain in accurately measuring its impact to provide a stronger evidence‐base. Standardisation of DAI service design, delivery and evaluation is required for future research and practice in providing holistic care for older adults.